Crassaminicella indica sp. nov., a novel thermophilic anaerobic bacterium isolated from a deep-sea hydrothermal vent. Issue 3 (23rd March 2023) - Jiao, Ze-Xi; Li, Xue-Gong; Zhang, Huan-Huan; Xu, Jun; Bai, Shi-Jie; Dai, Jie; Lin, Jin; Zhang, Wei-Jia; Qi, Xiao-Qing; Wu, Long-Fei
Abstract : A novel moderately thermophilic heterotrophic bacterium, designated strain 143-21 T, was isolated from a deep-sea hydrothermal chimney sample collected from the Central Indian Ridge at a depth of 2 440 m. Phylogenetic analysis indicated that strain 143-21 T belongs to the genus Crassaminicella . It was most closely related to Crassaminicella thermophila SY095 T (96.79 % 16S rRNA gene sequence similarity) and Crassaminicella profunda Ra1766H T (96.52 %). Genomic analysis showed that strain 143-21 T shares 79.79–84.45 % average nucleotide identity and 23.50–29.20 % digital DNA–DNA hybridization with the species of the genus Crassaminicella, respectively. Cells were rod-shaped, non-motile, Gram-positive-staining. Terminal endospores were observed in stationary-phase cells when strain 143-21 T was grown on Thermococcales rich medium. Strain 143-21 T was able to grow at 30–60 °C (optimum, 50 °C), pH 6.5–8.5 (optimum, pH 7.0) and in 1.0–7.0 % NaCl (w/v; optimum 2.0 %, w/v). Strain 143-21 T utilized fructose, glucose, maltose, mannose, ribose, N -acetyl-d -(+)-glucosamine and casamino acids, as well as amino acids including glutamate, lysine, histidine and cysteine. The main fermentation products from glucose were acetate (2.07 mM), H2 and CO2 . It did not reduce elemental sulphur, sulphate, thiosulphate, sulphite, fumarate, nitrate, nitrite and Fe (III). The predominant cellular fatty acids were C14 : 0 (48.8 %), C16 : 0 (12.9 %), and summed feature 3 (C16 : 1  ω7 c and/or C16 : 1  ω6 c ; 10.2 %). The major polar lipids were diphosphatidylglycerol, phosphatidylethanolamine and phosphatidylglycerol, as well as two unidentified phospholipids and four unidentified aminolipids. No respiratory quinones were detected. Based on its phylogenetic analysis and physiological characteristics, strain 143-21 T is considered to represent a novel species of the genus Crassaminicella, for which the name Crassaminicella indica sp. nov. is proposed. The type strain is strain 143-21 T (=DSM 114408 T = MCCC 1K06400 T ).